Optimized Substrates and Measurement Approaches for Raman Spectroscopy of Graphene Nanoribbons. Issue 12 (4th November 2019) - Overbeck, Jan; Borin Barin, Gabriela; Daniels, Colin; Perrin, Mickael L.; Liang, Liangbo; Braun, Oliver; Darawish, Rimah; Burkhardt, Bryanna; Dumslaff, Tim; Wang, Xiao-Ye; Narita, Akimitsu; Müllen, Klaus; et al.
Abstract : The on‐surface synthesis of graphene nanoribbons (GNRs) allows for the fabrication of atomically precise narrow GNRs. Despite their exceptional properties which can be tuned by ribbon width and edge structure, significant challenges remain for GNR processing and characterization. Herein, Raman spectroscopy is used to characterize different types of GNRs on their growth substrate and track their quality upon substrate transfer. A Raman‐optimized (RO) device substrate and an optimized mapping approach are presented that allow for the acquisition of high‐resolution Raman spectra, achieving enhancement factors as high as 120 with respect to signals measured on standard SiO2 /Si substrates. This approach is well suited to routinely monitor the geometry‐dependent low‐frequency modes of GNRs. In particular, the radial breathing‐like mode (RBLM) and the shear‐like mode (SLM) for 5‐, 7‐, and 9‐atom‐wide armchair GNRs (AGNRs) are tracked and their frequencies are compared with first‐principles calculations. Abstract : Raman spectroscopy is used to characterize armchair graphene nanoribbons on their growth substrate and after substrate transfer. A Raman‐optimized device substrate and an optimized mapping approach for the acquisition of high‐resolution, high signal‐to‐noise Raman spectra are presented. The achieved signal enhancement factors up to 120 with respect to measurements on SiO2 /Si substrates allow the detection of low‐intensity Raman modes.